Resveratrol Supplementation Prevents Hypertension in Hypertensive Pregnant Rats by Increasing Sodium Excretion and Serum Nitric Oxide Level. (22nd January 2020) - Jia, Xiaowen; Zhang, Rong; Guo, Jinzhu; Yue, Hua; Liu, Qiuxia; Guo, Lipei; Zhang, Qunchang
Abstract : Background . Pregnancy-induced hypertension (PIH) remains a major cause of morbidity and mortality in pregnancy worldwide. This study was designed to study the blood pressure-lowering effect of resveratrol (RES) in a salt-induced hypertensive pregnant rat model. Methods . Forty female Sprague Dawley (SD) rats were randomized into 4 groups: Normal Preg (0.9% salt diet), Normal Preg + RES (0.9% salt diet plus daily oral RES for 4 weeks), Salt Preg (8% salt diet), and Salt Preg + RES (8% salt diet plus daily oral RES for 4 weeks). Noninvasive blood pressure was recorded on gestational days 7 and 14. On the gestational day 19, foetuses were weighed, and blood and urine samples were harvested for electrolytes and biochemical assays. Results . RES significantly reduced SBP, DBP, and MAP on gestational days 7 and 14 in the Salt Preg + RES group compared to the Salt Preg group (all P < 0.05 ). Compared to the Salt Preg group, the foetal weight, serum NO level, urinary sodium, and 24 hour urine volume were significantly increased in the Salt Preg + RES group (all P < 0.05 ). On the contrary, the levels of serum urea, serum creatinine, and urinary protein were significantly decreased in the Salt Preg + RES group compared to the Salt Preg group (all P < 0.05 ). Conclusions . RES decreases blood pressure in a hypertensive pregnant rat model. Increasing sodium excretion and serum nitric oxide level might be, at least part of, the underlying mechanisms.